(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the currently available resources and conditions for implementing telemedicine activities under the Scheme for Remote Medical Examination and Treatment for 2020 – 2025. Research methods: This is a cross-sectional descriptive study conducted from October 2021 to December 2022. The data is compiled and analyzed from available data reports of 28/32 high-level hospitals and 49/63 Provincial Health Departments. In addition, the study has selected 05 centrallevel hospitals and 17 lower-level hospitals in 5 provinces/cities. Research results: (1) Lack of room for remote medical consultation, medical examination, and treatment compared to demand; The software is unstable and does not connect with other software in hospitals; Lack of secured solutions for patient information. (2) Lack of IT human resources, especially at the district level; Medical personnel has not been trained in operating the remote medical examination and treatment system. (3) Hospitals have not been able to collect fees or be paid by health insurance for remote medical examination and treatment services because there is no detailed instruction on the fee for services and payment methods. Conclusion: The conditions for implementing telemedicine, including IT systems, human resources and finance, are all limited compared to necessary needs, so telemedicine activities are only at the initial level and not synchronized. Proposed solutions: To improve the legal basis for remote medical examination and treatment; To continue to strengthen IT organizations and human resources and train medical professionals in IT; To construct the mechanism to ensure funding sources for investment and maintenance of the IT system; To support to connect the information technology infrastructure to maintain the efficiency and sustainability of remote medical examination and treatment services.